2020
DOI: 10.1002/prp2.612
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐derived dopamine modulates EFS‐induced contractions of human umbilical vessels

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…Furthermore, the EFS-induced contractions were also blocked by D2-like receptor antagonists, indicating that release of dopamine plays a major role on this phenomenon. The contractions induced by EFS in human umbilical artery and vein are also blocked by D 2 -like receptor antagonists, but not affected by the D 1 -receptor antagonist SCH-23390 ( Britto-Junior et al, 2020b ). The inhibition of EFS-induced contractions by the D 2 -like receptor antagonist haloperidol reveals an important modulatory role of the endothelium-derived dopamine, acting as a vasoconstrictor through the D2-like receptors.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the EFS-induced contractions were also blocked by D2-like receptor antagonists, indicating that release of dopamine plays a major role on this phenomenon. The contractions induced by EFS in human umbilical artery and vein are also blocked by D 2 -like receptor antagonists, but not affected by the D 1 -receptor antagonist SCH-23390 ( Britto-Junior et al, 2020b ). The inhibition of EFS-induced contractions by the D 2 -like receptor antagonist haloperidol reveals an important modulatory role of the endothelium-derived dopamine, acting as a vasoconstrictor through the D2-like receptors.…”
Section: Discussionmentioning
confidence: 92%
“…The results presented here clearly demonstrate, for the first time in the tortoise, that Chelonoidis carbonaria aortae have a basal release of dopamine, noradrenaline and adrenaline, as identified by tandem mass spectrometry, and the amount released is significantly reduced by endothelium-removal. Basal release of endothelium-derived catecholamines also occur in human umbilical vessels ( Britto-Júnior et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pre-contracted human umbilical vessels ( 4 ) and in Chelonoidis carbonarius aortic rings ( 5 ), the relaxations induced by 6-ND were similar to those induced by the dopamine D 2 -like receptor antagonist haloperidol, since they were not affected by pre-incubation with L-NAME but strongly reduced in endothelium-denuded rings. Dopamine is released by cultured endothelial cells ( 23 ), human umbilical cord arteries and vein ( 24 ), and Chelonoidis carbonaria aortic rings ( 25 ). Indeed, immunohistochemistry for tyrosine hydroxylase of both Crotalus durissus terrificus and Bothrops jararaca aortae revealed that this enzyme is present in endothelial cells ( 26 ).…”
Section: Discussionmentioning
confidence: 99%